Iterative receiver with enhanced channel estimator for imperfect ISI channel - Tan, Timmy Yong Khim. (2008)
In mobile radio links, the imperfect estimates of the channel impulse response and the time-variant intersymbol interference (ISI) caused by time-varying frequency-selective multipath phenomena will cause severe degradation in the performance of a communication system. The objective of this thesis is to find a method to reduce these undesirable effects.